IDO Inhibitor and Gallic Acid Cross-Linked Small Molecule Drug Synergistic Treatment of Melanoma - Liu, Hongmei; Gao, Huan; Chen, Cheng; Jia, Wenyu; Xu, Delong; Jiang, Guan (Frontiers in Oncology, 2022)
In this study, we synthesized a molecule GA-1MT (GM) composed of indoleamine 2,3-dioxygenase (IDO) inhibitor (1-methyl-d-tryptophan, 1MT) called NLG8189 and gallic acid (GA) and verified its therapeutic effect on B16F10 melanoma cells and an orthotopic tumor-bearing mouse model. The synthesized molecule GM was analyzed by 1H NMR and mass spectrometry (MS). In addition, we confirmed that GM could mediate the immune response in the B16F10 cell tumor model by flow cytometry and immunofluorescence. The synthesized GM molecule could increase the solubility of 1MT to enhance the drug efficacy and lower costs. Moreover, GM could inhibit melanoma growth by combining 1MT and GA. In vivo experiments showed that GM could effectively inhibit the expression of tyrosinase, regulate the proportion of CD4+ T cells, CD8+ T cells, and regulatory T cells (Treg cells) in tumors, and significantly suppress melanoma growth. The newly synthesized drug GM could more effectively inhibit melanoma than GA and 1MT alone or in combination.